An Evaluation of the Effect of Stimulation Parameters and Electrode Type on Bicep Muscle Response for a Voltage-controlled Functional Electrical Stimulator. Issue 1 (July 2017) - Stewart, Ashley M.; Pretty, Christopher G.; Chen, XiaoQi
Abstract: Millions of dollars worldwide are spent on electrodes for Functional Electrical Stimulation (FES) every year. With aging populations the increasing costs faced by healthcare providers are of significant concern. Conventional electrodes used for FES are of limited use and deteriorate with use. Washable E-textile electrodes have recently been used successfully for monitoring applications such as electromyography (EMG). E-textile electrodes could potentially reduce the costs faced by healthcare providers. However limited investigation has been conducted into the use of e-textile electrodes for actuation applications such as FES. This paper compares the effectiveness of e-textile electrodes with conventional hydrogel electrodes at a range of stimulation parameters. The electrodes performed similarly under variation of frequency (20-50 Hz) and ramp rate parameters (2-10 V/s). The e-textiles produced a stronger response at a lower voltage than the hydrogels (3-4 V difference for a stimulation intensity voltage range of 8-22 V), however they must be wet to work which may be a barrier to their uptake.